LUPIYA WARNI-WARNI KOLEKSI MUSEUM SONOBUDOYO PB A.20 (SUNTINGAN TEKS DAN TERJEMAHAN) - , SEISAR WINENGKU HANDANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The manuscript entitled Lupiya Warni-Warni (LWW) is one of the collections of Sonobudoyo Musseum in Yogyakarta code cillection PB A. 40. LWW was written in Javanese characters as well as language. It is in form of macapat and prose. A macapat consist of 6 strophes while a prose is one page. LWW contains with varian contens, wich are the letters of princesses in Kraton to Raden Ayu SÄdah Mirah on her birthday, the symbolic stories of Javanese characters, primbon, prohibited action during coitus, Prophet Muhammads advices to his daughter and his son in-law Sayid Ali about coitus, advices in coexisting with other fellow human being, the five pillas teeaching, and the note from Kanjeng Sinuhun Susuhunan. This reasearch focuses on the text editing and translation. The editing method occupied in this reasearch is improve text. Its is followed by the aims of translating the text to increase the degree of understanding the text